IMPLEMENTASI SISTEM INFORMASI ARSIP DIGITAL UNTUK MANAJEMEN DATA BMKG WILAYAH 1 MEDAN - Samsudin; Pria Mitra Purba (Program Studi Informatika Universitas Teknologi Sumbawa, 2023)
This research aims to improve the efficiency of data management at the Meteorology, Climatology and Geophysics Agency (BMKG) Region 1 Medan through the implementation of a web-based digital archive information system using PHP and local databases. The research objectives include handling the problems of manual archival storage and data input using Excel. The system design, including flowmaps, use case diagrams, and development with PHP, was successfully implemented to improve accessibility and data management in the organization. The benefits of this research involve solutions to the problem of effective archive storage and management, supporting more informed decisions, and increasing the productivity of BMKG Region 1 Medan. In its implementation, this system helps minimize the risk of loss and damage to important data. Keywords : Digital Archives Information System, BMKG Region 1 Medan, Archives Management